A comprehensive evaluation of the WSGG model for air- and oxy-fuel combustion conditions through three-dimensional calculations. (October 2021) - Fraga, G.C.; Silva, F.R.; Zanin, L.G.B.; da Fonseca, R.J.C.; França, F.H.R.; Centeno, F.R.
Abstract: This paper reports an assessment of the accuracy of most formulations of the weighted-sum-of-gray-gases (WSGG) model proposed in the last decade for the treatment of mixtures of water vapor and carbon dioxide. The analysis is based on non-coupled, three-dimensional radiative transfer calculations of cases representative of air- and oxy-fuel combustion at fixed or varying H2 O–CO2 mole fraction ratios ( MR ). The reference solution is computed by line-by-line (LBL) integration. The WSGG model is shown as capable to provide accurate results for all cases under study, with existing correlations for the model displaying maximum errors below 4%. Formulations developed considering MR variations can in general be safely used even for cases where MR is constant; likewise, fixed- MR correlations can be applied for varying- MR scenarios, as long as the regions of most importance for the radiative transfer have a MR value close to the one for which the correlations were generated. The superposition WSGG model is tested as well, and it yields consistently accurate results for all test cases, although at a significantly larger processing cost than the standard WSGG model. An alternative approach for treating media with varying mole ratio, consisting of interpolating fixed- MR correlations, is also found to be promising.